A mechanistic model of mismatch negativity in the ageing brain - Cooray, Gerald; Garrido, Marta I.; Hyllienmark, L.; Brismar, Tom (Clinical neurophysiology, 2014)
•We investigated the cortical network generating the mismatch negativity (MMN) in the ageing brain using dynamic causal modelling.•The ageing brain showed changes in connectivity between temporal and frontal regions together with a frontal dysregulation of the excitatory–inhibitory balance.•This study provides for the first time a neurobiological explanation for the age related changes of the MMN in the ageing brain. We investigated the neurophysiological mechanisms underpinning the generation of the mismatch negativity (MMN) in the ageing brain. We used dynamic causal modelling (DCM) to study connectivity models for healthy young and old subjects. MMN was elicited with an auditory odd-ball paradigm in two groups of healthy subjects with mean age 74 (n=30) and 26 (n=26). DCM was implemented using up to five cortical nodes. We tested models with different hierarchical complexities. We showed that the network generating MMN consisted of 5 nodes that could modulate all intra- and inter-nodal connections. The inversion of this model showed that old subjects had increased input from rSTG to the rIFG (p<0.01) together with increased inhibition of pyramidal cells (p<0.05). Furthermore, there was reduced modulation of activity within rIFG (p<0.02) on stimulus change. The age related change in MMN is due to a decline in frontal-based control mechanisms, with alterations in connectivity between temporal and frontal regions together with a dysregulation of the excitatory–inhibitory balance in the rIFG. This study provides for the first time a neurobiological explanation for the age related changes of the MMN in the ageing brain.